Quantum Blue Reduces the Severity of Woody Breast Myopathy via Modulation of Oxygen Homeostasis-Related Genes in Broiler Chickens - Greene, Elizabeth; Flees, Joshua; Dadgar, Sina; Mallmann, Barbara; Orlowski, Sara; Dhamad, Ahmed; Rochell, Samuel; Kidd, Michael; Laurendon, Caroline; Whitfield, Hayley; Brearley, Charles; Rajaram, Narasimhan; et al. (Frontiers in Physiology, 2019)
The incidence of woody breast (WB) is increasing on a global scale representing a significant welfare problem and economic burden to the poultry industry and for which there is no effective treatment due to its unknown etiology. In this study, using diffuse reflectance spectroscopy (DRS) coupled with iSTAT portable clinical analyzer, we provide evidence that the circulatory-and breast muscle-oxygen homeostasis is dysregulated (low oxygen and hemoglobin levels) in chickens with WB myopathy compared to healthy counterparts. Molecular analysis showed that blood hemoglobin subunit Mu (HBM), Zeta (HBZ), and hephaestin (HEPH) expression were significantly down regulated, however the expression of the subunit rho of hemoglobin beta (HBBR) was upregulated in chicken with WB compared to healthy counterparts. The breast muscle HBBR, HBE, HBZ, and hypoxia-inducible factor prolyl hydroxylase 2 (PHD2) mRNA abundances were significantly down regulated in WB compared to normal birds. The expression of HIF-1α at mRNA and protein levels was significantly induced in breasts of WB-affected compared to unaffected birds confirming a local hypoxic status. The phosphorylated levels of the upstream mediators AKT at Ser473 site, mTOR at Ser2481 site, and PI3K P85 at Tyr458 site, as well as their mRNA levels were significantly increased in breasts of WB-affected birds. In attempt to identify a nutritional strategy to reduce WB incidence, male broiler chicks were randomly distributed into 48 floor pens and subjected to six treatments: a nutrient adequate control group (PC), the PC supplemented with 0.3% myo-inositol, a negative control deficient in available P and Ca , the NC fed with quantum blue (QB) at 500, 1,000 or 2,000 FTU/kg of feed. Although QB-enriched diets did not affect growth performances (FCR and FE), it did reduce the severity of WB by 5% compared to the PC diet. This effect is mediated by reversing the expression profile of oxygen homeostasis-related genes; i.e. significant down regulation of HBBR and upregulation of HBM, HBZ, and HEPH in blood, as well as a significant upregulation of HBA1, HBBR, HBE, HBZ, and PHD2 in breast muscle compared to the positive control.